PENGARUH INOVASI DAN DAYA TARIK TERHADAP KEPUTUSAN BERKUNJUNG DI THE L HOTEL ENTERTAINMENT BATAM - Lature, Agnes Filadelfia; Realize, Realize (SCIENTIA JOURNAL, 2023)
Tourism is an important economic sector for Indonesia because it provides a large foreign exchange for the country. The hotel is an object in the tourism sector, therefore hotel management must carry out cooperation with other supporters so that guests can recognize it. The hospitality business has become an industry that continues to grow as well as the rapid transformation of the Riau Archipelago from the manufacturing industry to the tourism industry. In order to maintain its business in competition, the management of L Hotel Batam must improve its company's ability to remain competitive, one of the ways is by paying attention to the factors that influence the visitor's decision to visit. The purpose of this study was to determine the effect of innovation and attractiveness on the decision to visit The L Hotel Entertainment. This research was conducted using quantitative techniques. The research sample used 306 respondents, namely visitors to the L Hotel for the period March 2023 who were over 17 years old. Questionnaires are used as data collection techniques. The conclusion of this research is that the innovation and attractiveness variables influence the decision to visit with the acquisition of sig. 0.00 < 0.05. In addition, innovation and attractiveness influence the decision to visit by 40.9% which is found from the results of the coefficient of determination test. Based on the results of hypothesis testing, it was found that innovation and attractiveness partially and simultaneously had a positive and significant effect on the decision to visit The L Hotel Entertainment.